Detection of the secondary, low-affinity β(1)-adrenoceptor site in living cells using the fluorescent CGP 12177 derivative BODIPY-TMR-CGP - Gherbi, K (Br J Pharmacol, 2014)
BACKGROUND AND PURPOSE: CGP 12177 not only inhibits agonist effects mediated through the catecholamine site of the β(1)-adrenoceptor with high affinity, but also exhibits agonist effects of its own at higher concentrations through a secondary, low-affinity β(1)-adrenoceptor site or conformation. β-blocker affinities for this ‘CGP 12177’ site of the human β(1)-adrenoceptor have thus far only been characterized in functional studies. Here, we used the fluorescent CGP 12177 analogue BODIPY-TMR-CGP to directly investigate receptor–ligand interactions at the secondary binding site of the β(1)-adrenoceptor. EXPERIMENTAL APPROACH: The human β(1)-adrenoceptor was stably expressed in CHO cells containing a cAMP response element (CRE)-secreted placental alkaline phosphatase (SPAP) reporter gene construct. Functional responses of BODIPY-TMR-CGP were determined in the CRE-SPAP reporter gene assay, and manual and automated confocal microscopy platforms used to investigate the binding properties of BODIPY-TMR-CGP. KEY RESULTS: BODIPY-TMR-CGP displayed a pharmacological profile similar to that of CGP 12177, retaining agonist activity at the secondary β(1)-adrenoceptor site. In confocal microscopy studies, specific BODIPY-TMR-CGP binding allowed clear visualization of β(1)-adrenoceptors in live cells. Using a wider concentration range of labelled ligand in a high-content fluorescence-based binding assay than is possible in radioligand binding assays, two-site inhibition binding curves of β-adrenoceptor antagonists were revealed in CHO cells expressing the human β(1)-adrenoceptor, but not the β(2)-adrenoceptor. CONCLUSIONS AND IMPLICATIONS: The fluorescent CGP 12177 analogue allowed the detection of the β(1)-adrenoceptor secondary site in both functional and binding studies. This suggests that BODIPY-TMR-CGP presents an important and novel fluorescent tool to investigate the nature of the secondary β(1)-adrenoceptor site.